Hounded - Hearne, Kevin (Hearne, Kevin. Iron druid chronicles., 2011)
Atticus O'Sullivan, the last of the Druids, finds his peaceful life in Arizona shattered by the arrival of an angry Celtic god who wants Atticus's magical sword, forcing Atticus to call upon some unlikely allies for help.